2017
DOI: 10.1073/pnas.1706394114
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of caveolin-1 in ocular neovascularization and multitargeted antiangiogenic effects of cavtratin via JNK

Abstract: Ocular neovascularization is a devastating pathology of numerous ocular diseases and is a major cause of blindness. Caveolin-1 (Cav-1) plays important roles in the vascular system. However, little is known regarding its function and mechanisms in ocular neovascularization. Here, using comprehensive model systems and a cell permeable peptide of Cav-1, cavtratin, we show that Cav-1 is a critical player in ocular neovascularization. The genetic deletion of Cav-1 exacerbated and cavtratin administration inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…They found that the combined administration of cavtratin and anti-VEGF-A (the usual treatment for DR) inhibited neovascularization more effectively than monotherapy. Cavtratin exerts its effect by downregulating eNOS expression and the platelet-derived growth factor-B (PDGF-B) in vivothrough the JNK pathway [213]. These two factors play important roles in pathological angiogenesis [214,215].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…They found that the combined administration of cavtratin and anti-VEGF-A (the usual treatment for DR) inhibited neovascularization more effectively than monotherapy. Cavtratin exerts its effect by downregulating eNOS expression and the platelet-derived growth factor-B (PDGF-B) in vivothrough the JNK pathway [213]. These two factors play important roles in pathological angiogenesis [214,215].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the retina, Cav1 affects important visual processes such as phagolysosomal digestion of photoreceptor outer segments by the retinal pigment epithelium (RPE) (16), maintenance of retinal vascular blood-retinal-barrier integrity (17)(18)(19), and retinal neovascularization (20). We and others have also implicated Cav1 function specifically in retinal inflammation and immune response modulation (21)(22)(23).…”
mentioning
confidence: 99%
“…Chen demonstrated the primary colocalization of DDAH1 and Caveolin-1 in the endothelium of cardiac microvessels (18). In fact, Caveolin-1 is mainly expressed in endothelial cells (34). It is conceivable that similar localization of DDAH1 and Caveolin-1 substantiates the same function in regulating cardiac angiogenesis.…”
Section: Discussionmentioning
confidence: 91%